1998
DOI: 10.1901/jaba.1998.31-529
|View full text |Cite
|
Sign up to set email alerts
|

Fixed‐time Schedules Attenuate Extinction‐induced Phenomena in the Treatment of Severe Aberrant Behavior

Abstract: We compared the effects of extinction (EXT) and fixed-time (FT) schedules as treatment for severe problem behavior displayed by 3 individuals with developmental disabilities. First, functional analyses identified the reinforcers maintaining aberrant behavior for all 3 individuals. Next, EXT and FT schedules were compared using a multielement design. During EXT, the reinforcer maintaining problem behavior was withheld. During FT, the reinforcers were presented response independently at preset intervals. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 18 publications
2
47
1
Order By: Relevance
“…A second implication for treatment is highlighted by Jimmy's results. Given the continuation of responding during FT schedules, the addition of brief differential reinforcement of other behavior (e.g., Vollmer et al, 1998) might be warranted. Adding this component would reduce the probability of adventitious reinforcement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second implication for treatment is highlighted by Jimmy's results. Given the continuation of responding during FT schedules, the addition of brief differential reinforcement of other behavior (e.g., Vollmer et al, 1998) might be warranted. Adding this component would reduce the probability of adventitious reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“…Once stable responding was observed across sessions, the experimental conditions were conducted. This FR 1 baseline condition is analogous to the baseline conditions described in many treatment studies, in which each occurrence of a target behavior results in reinforcer delivery (e.g., Vollmer et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Vollmer et al (1998) compared the effects of extinction with and without NCR and found that extinction, when implemented alone, was associated with bursts of behavior for 2 of the 3 participants, whereas extinction with NCR was not.…”
mentioning
confidence: 99%
“…To isolate the enhancing effects of competing stimuli, it would be necessary to evaluate the effects of competing stimuli with extinction relative to a condition in which extinction was implemented alone, just as Vollmer et al (1998) evaluated the enhancing effects of NCR by comparing NCR plus extinction with extinction alone. In the current investigation, we extended the results of Hanley et al and replicated the results of Vollmer et al by comparing the effects of (a) extinction implemented alone, (b) extinction implemented with noncontingent delivery of the reinforcer that maintained destructive behavior (attention), and (c) extinction implemented with noncontingent delivery of competing stimuli (those identified through the competing stimulus assessment).…”
mentioning
confidence: 99%
“…However, because it is reasonable to conclude that using the term NCR has served a useful purpose, some authors may be inclined to continue its use because of convention. Although I now use schedule descriptors in my own work (e.g., Vollmer et al, 1998), I am not entirely content using them. -time (event), for example, does not capture the generality of the procedures, nor does it capture an essential property of the treatment: The noncontingent event bears a known functional relationship to the target behavior.…”
Section: Journal Of Applied Behavior Analysismentioning
confidence: 99%